2017
DOI: 10.1177/1744806917703111
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated kinase and the endogenous endocannabinoid system might contribute to antinociceptive effects of prolonged moderate caloric restriction in mice

Abstract: BackgroundCaloric restriction is associated with broad therapeutic potential in various diseases and an increase in health and life span. In this study, we assessed the impact of caloric restriction on acute and inflammatory nociception in mice, which were either fed ad libitum or subjected to caloric restriction with 80% of the daily average for two weeks.ResultsThe behavioral tests revealed that inflammatory nociception in the formalin test and in zymosan-induced mechanical hypersensitivity were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Notably, CR consisting of 80% of the daily intake for two weeks did not influence AEA levels of C57Bl6J mice in one previous study [ 38 ]. We assumed this difference to be the result of a more stringent CR protocol (i.e., a longer period of lower calorie intake in the study at hand).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Notably, CR consisting of 80% of the daily intake for two weeks did not influence AEA levels of C57Bl6J mice in one previous study [ 38 ]. We assumed this difference to be the result of a more stringent CR protocol (i.e., a longer period of lower calorie intake in the study at hand).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, the literature concerning dietary influences on AEA in humans is much more controversial than in rodents [ 38 ] or C. elegans [ 27 ]. Therefore, we analyzed human serum samples acquired before and after short-term CR in three independent cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…148 In addition to the standard CR regime, 2-week CR with 80% of average daily consumption reduced mechanical hypersensitivity in both the formalin test and the zymosan-induced paw inflammation model. 149 Researchers using transgenic mice found that the effects of CR in attenuating pain perception were related to activation of both AMPK signaling and the endogenous endocannabinoid system. 149 Moreover, a 3-month intermittent fasting diet (IFD) significantly reduced pain responses in mice in thermal and visceral pain models compared to the ad libitum control group.…”
Section: Cr In Inflammatory Painmentioning
confidence: 99%
“…149 Researchers using transgenic mice found that the effects of CR in attenuating pain perception were related to activation of both AMPK signaling and the endogenous endocannabinoid system. 149 Moreover, a 3-month intermittent fasting diet (IFD) significantly reduced pain responses in mice in thermal and visceral pain models compared to the ad libitum control group. 150 Expression levels of prodynorphin and κ-opioid receptors were upregulated.…”
Section: Cr In Inflammatory Painmentioning
confidence: 99%
“…AMPK activation in the CNS has also been linked to positive outcomes in chronic pain models with some of the most compelling evidence linking AMPK activation to enhance glutamate clearance via an astrocyte-mediated mechanism (Maixner et al, 2015). Finally, a very recent study has linked AMPK activation to the beneficial effects of exercise on chronic pain (King-Himmelreich et al, 2017). Collectively these studies point to a very positive outlook for the potential of developing potent and specific AMPK activators for the treatment of pain.…”
Section: The Potential Of Specific Translation Signaling Mechanisms Amentioning
confidence: 99%